Recurrent Colonic Perforation in Geriatric Patients with Sigmoid Colostomy: Two Case Reports - Hyeonkyeong Kim; Kwang Ho Kim; Gyoung Tae Noh; Ho Seung Kim (The Ewha Medical Journal)
Recurrent colonic perforation in patients already having colostomy is extremely rare and only a few cases had been reported. Herein, we report 2 cases of recurrent colonic perforation at the proximal part of the colostomy in geriatric patients resulting from different causes, which might be caused by stercoral perforation and recurrent colonic ischemia, respectively. Based on our experience, surgeons should consider correcting chronic constipation even in patients who already have a colostomy. Additionally, transverse colostomy should be considered as a surgical treatment in patients with sigmoid colostomy for recurrent perforation due to colonic ischemia.